The Role of Work Discipline in Mediating the Influence of Work Environment and Leadership on Employee Performance at BUMDES Barokah, Pulau Lawas Village, Bangkinang District - Habibie, Indra; Nurkholis; Akbar, Rahmad; Yetti, Dzulhijjah; Azhari (Journal of Engineering Science and Technology Management, 2025)
This research aims to analyze how the work environment and leadership influence employee performance, with work discipline serving as a mediating factor. The study was conducted at BUMDes Barokah, located in Pulau Lawas Village, Bangkinang District. A quantitative approach was used, involving 30 employees selected through a census technique. Data collection was carried out using a questionnaire, and analysis employed multiple regression and Sobel test to examine the mediation effect. The results show that both the work environment and leadership have a positive and significant impact on employee performance. Additionally, work discipline significantly mediates the relationship between these two variables and performance outcomes. This indicates that a supportive work environment and effective leadership must be complemented by strong employee discipline to improve performance. The findings suggest that BUMDes management should focus on creating a conducive workplace and applying participative leadership while also strengthening work discipline to enhance productivity and achieve organizational goals.